The Effect of Return on Asset , Return on Equity , Net Profit Margin , and Debt to Equity Ratio on Dividen in Pharmaceutical Companies in Period 2017 – 2021 - Arlita Ayu Fricila; Agus Sukoco (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: This research is based on a phenomenon that occurs from the impact of the Covid-19 pandemic which causes an increase in the consumption of medicines in all levels of society due to efforts to increase immunity to prevent corona virus infection and to see the company's ability to predict future opportunities and strategies is the main key in the success of a company. Companies are also required to innovate products, especially during the Covid-19 pandemic and pharmaceutical companies are intensively innovating products because people are aware of the importance of maintaining health. This study aims to determine the effect of Return On Asset, Return On Equity, Net Profit Margin, and Debt To Equity Ratio on Dividend Payout Ratio. Design/methodology/approach: The independent variables in this study are ROA (X1), ROE (X2), NPM (X3) and DER (X4) and the dependent variable in this study is DPR (Y). The type of research used in this study is a type of quantitative research. This study took all time series data with a period of 5 years 2017 to 2021. The number of research samples with purposive sampling techniques was obtained by as many as 5 companies. Findings: From the results of this study, it can be concluded that ROA, ROE, NPM, and DER have a significant effect on DPR. Originality/value: This paper is original Paper type: Research paper